ANALISIS RESEPSI PENONTON TERHADAP DUKUNGAN BAGI KORBAN KEKERASAN SEKSUAL DALAM SERIAL UNBELIEVABLE - Nadifah, Roudotun (The Commercium, 2024)
Sexual violence can be happened anywhere, both in public and domestic spaces. It can also happen to anyone regardless of age, gender or social background. In this research, researcher focus on discussing the issue of sexual violence that occurs against women in the domestic space which is show in the form of the Netflix film series "Unbelievable". Then, it was analyzed using the reception method from Stuart-Hall through a descriptive-qualitative approach. It was found, that among the audiences who were either directly or indirectly have a role in handling cases of sexual violence, one of them was reproduced all the messages the meaning sent by encoder (opposition). Some of them fully support (dominant hegemony) and others negotiate (negotiative) the content of messages regarding the environment that support what happen on victims of sexual violence, that shown by the media is in accordance with the social reality that they believe is fully true. However, there are still some messages that cannot be applied in reality due to several factors such as social norms, knowledge or different backgrounds. Even so, the audiences can still freely interpret the meaning of the message according to their own knowledge and experience.